Kinerja Petugas Kantor Depan Dalam Memaksimalkan Guest Voice Pada Masa Pandemi Covid-19 Di The Laguna A Luxury Collection Resort And Spa - Ni Nengah Trisna Prawiti; I Gusti Ayu Putu Wita Indrayani; I Gusti Ayu Niken Launingtya (Journal of Hospitality Accommodation Management (JHAM), 2022)
This research aims to understand receptionist performance to maximize intent to recommend and staff service in The Laguna, A Luxury Collection Resort and Spa. Performance assessment based on performance dimensions by Mangkunegara consists of quality, quantity, task execution, and responsibility. The data obtained by an in-depth interview with two informants with qualitative analysis techniques is presented descriptively. The result showed that receptionist performance based on the dimensions of quality, quantity, and task execution was not maximally implemented, whereas the dimension of responsibility was maximally implemented. In general, receptionist performance is not maximally implemented in order to maximize the intent to recommend and staff service in The Laguna, A Luxury Collection Resort and Spa. Suggestions for the Front Office Department to be aware of the result of the realization of intent to recommend and staff service through periodic evaluation to encourage receptionists to improve their performance. Keywords: performance, receptionist, guest voice, intent to recommend, staff service, pandemic